1994
DOI: 10.1002/cber.19941270507
|View full text |Cite
|
Sign up to set email alerts
|

Metallkomplexe funktioneller Isocyanide, XXIV. Reaktionen von N‐Isocyandialkylamin‐Metallkomplexen mit sekundären Aminen

Abstract: Diese dem Curtius-Abbau analoge Reaktionsbeschreibung wird durch weitere Beobachtungen gestutzt: Verfolgt man die Reaktion IR-spektroskopisch, so treten nach sehr kurzen Reaktionszeiten Banden auf, die von Amino(hydrazino)carben-Komplexen stammen konnen. Bei langeren Reaktionszeiten und hohem Aminuberschulj finden sich im Rohprodukt IR-Banden, die wir nichtkoordiniertem Cyanamid zuordnen konnen (vgl. dazu 2.). Mit sterisch anspruchsvollen Dialkylaminen wie Diisopropylamin, Dicyclohexylamin oder 2,6-Dimethylpip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Work-up finally resulted in two products: the isomeric (N-cyanoimino)triphenylphosphorane (4), which has already been synthesised by Appel and co-workers and was identified on the basis of its elementary analysis, its melting point and its IR data, [23,24] and a second pale -yellow compound 10, which was recrystallised from dichloromethane/ diethyl ether and showed the same analytical composition but double the molecular mass. The IR spectrum with a weak to medium intensity band at 2200 cm 31 P NMR spectrum, which contains two singlets at δ = 24 and 11 ppm, are in perfect agreement with the suggested structure for 10.…”
Section: Cn/nc Isomerisations Of (N-isocyanimino)-triphenylphosphoransupporting
confidence: 78%
See 1 more Smart Citation
“…Work-up finally resulted in two products: the isomeric (N-cyanoimino)triphenylphosphorane (4), which has already been synthesised by Appel and co-workers and was identified on the basis of its elementary analysis, its melting point and its IR data, [23,24] and a second pale -yellow compound 10, which was recrystallised from dichloromethane/ diethyl ether and showed the same analytical composition but double the molecular mass. The IR spectrum with a weak to medium intensity band at 2200 cm 31 P NMR spectrum, which contains two singlets at δ = 24 and 11 ppm, are in perfect agreement with the suggested structure for 10.…”
Section: Cn/nc Isomerisations Of (N-isocyanimino)-triphenylphosphoransupporting
confidence: 78%
“…[28] Actually, all the necessary "instruments" are there: thus, we have shown that N-isocyanides are prone to nucleophilic attack even in less activating metal complexes, [8,29] 3 carries a strong nucleophile in the form of the imino nitrogen, and N-N cleavage is a common occurrence in N-isocyanide chemistry. [17,30,31] …”
Section: Cn/nc Isomerisations Of (N-isocyanimino)-triphenylphosphoranmentioning
confidence: 98%
“…Attempts to alkylate 8 / 8’ did not lead to defined products; a feature in the infrared at 2110 cm –1 [ν(CN)?] probably indicates ring opening via N–N cleavage, a process very common in N‐isocyanide chemistry 34. Methylation of 10 with iodomethane, on the other hand, appears to occur at the exo ‐S atom (as assessed by X‐ray, e.g., for the methylation product of 12a 28).…”
Section: Resultsmentioning
confidence: 99%
“…[511,512]). [530] Even more conformity with the chemistry under discussion displays Fischer's reaction with N 3 -of an aminocarbyne complex 110 (Equation (37)), frequently misinterpreted as a metal-bound isocyanide; [51] in reality we are dealing with a model "metalla-dipolarophile", which perfectly fits into the mechanism depicted in Equation (38) (see below). The authors, however, preferred a reaction course via intermediate amino(azido)-and amino(nitrene)carbene complexes, the latter of which immediately rearranges to the final product.…”
Section: Functional Isocyanidesmentioning
confidence: 96%